Enhanced densification and dielectric properties of CaTiO3-0.3NdAlO3 ceramics fabricated by direct coagulation casting. Issue 4 (April 2020) - Chen, An-Nan; Wu, Jia-Min; Cheng, Li-Jin; Liu, Shao-Jun; Ma, Yi-Xin; Li, Hao; Liu, Fei; Chen, Shuang; Shi, Yu-Sheng; Li, Chen-Hui
Abstract: Severe sintering conditions always cause defects that increase the dielectric loss of microwave ceramics. Direct coagulation casting (DCC) of submicron powder suspension, was applied to accelerate densification and enhance dielectric properties of 0.7CaTiO3 -0.3NdAlO3 (CTNA) ceramics. The rapid in-situ coagulation of suspension was achieved by tailoring the pH value to the isoelectric point to weaken the repulsion of electric double layer and steric hindrance effect. Compared with the dry-pressed samples, the DCC-fabricated samples are more compacted, which provides a high initial densification value and a shortened diffusion path, and consequently promotes the material transportation and composition homogenization that inhibits the segregation of CaAl12 O19 . Additionally, the submicron powders accelerate the phase transition and domains growth, leading to a significant reduction of lattice defects in microstructure. Therefore, Q⋅f value of CTNA ceramics reaches more than 40, 000 GHz, which is improved by 15 % compared with that of dry-pressed samples sintered under the same conditions.